(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The office procedure plays a vital role in the productivity of every department in any school. Deficiency in the office procedure may lead to problems and conflicts which affects the function and services of a certain department. This study focused on the improvement of the office procedure of Library Department, Guidance Department and Gymnasium in Bestlink College of the Philippines. The researchers attempted to determine the problems occurred in the said departments that need to be addressed for the benefits and advancement of the institution. Quantitative method was used in this research study to emphasize objective measurements and numerical analysis of data collected through surveys in using computational techniques. The researchers conducted interviews and surveys to the staff of the selected departments. An interview was administered to the employees to obtain detailed information about their perception and opinions on the current situation inside their departments. Survey questionnaires were also used to get the accurate information about the problems. Based on the survey, the respondents agreed that the existing problems in Library Department include 1) insufficient number of staff; 2) incomplete content for library I.D. card and book card; 3) lack of follow-up process in case of failures in delivering the ordered books; 4) lack log book or record book for those people who borrowed and returned the books in the reception area and; 5) lack terms and conditions in the reservation slip for the reservation of the equipment (projector). In the Guidance Department, the researchers found out that the problems are 1) the counseling room is not suitable especially in main campus; 2) there is no psychometrician to handle the testing services and; 3) updating of the student information is done manually. On the other hand, the existing problems in Gymnasium Department stems predominantly from the absence of set policies. There is no existing rules and regulations in gymnasium, no proper monitoring for the maintenance of gymnasium, no proper schedule of use of the premise. These findings display the need for additional employees to hire for the selected departments. The researchers propose to enhance and upgrade the content of library card, book card, slip and logbook in Guidance and Library Department. The researchers also propose for proper scheduling and policies regarding the use of the gymnasium.